2014
DOI: 10.1590/0103-166x2014000300002
|View full text |Cite
|
Sign up to set email alerts
|

Rorschach e sofrimento psíquico grave: funcionamento psíquico nas primeiras crises psicóticas

Abstract: Estudos de Psicologia I Campinas I 31(3) I 337-345 I julho -setembro 2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Consequently, those Rorschach indexes that include FQ play an important role not only in the clinical setting, in which they can support diagnosis and help to understand the distress of the individual and on the prognosis and better treatment planning, but also in the research context. In fact, several recent studies have tested the psychometric properties of these indexes (Mihura, Meyer, Dumitrascu, & Bombel, 2013;Viglione, Giromini, Gustafson, & Meyer, 2014;Wood, Garb, Nezworski, Lilienfeld, & Duke, 2015), and applied them on several samples from different countries (DzamonjaIgnjatovic, Smith, Djuric Jocic, & Milanovic, 2013;Moore, Viglione, Rosenfarb, Patterson, & Mausbach, 2013;Silva & Costa, 2014). Valkonen, Lindfors, and Knekt (2012) used the Ego Impairment Index, EII, to study anxiety disorders, and found a significant, but weak association between the EII and the interview-based scale Level of Personality Organization, LPO, (Pyykkönen, 2008, apud Valkonen et al, 2012.…”
mentioning
confidence: 99%
“…Consequently, those Rorschach indexes that include FQ play an important role not only in the clinical setting, in which they can support diagnosis and help to understand the distress of the individual and on the prognosis and better treatment planning, but also in the research context. In fact, several recent studies have tested the psychometric properties of these indexes (Mihura, Meyer, Dumitrascu, & Bombel, 2013;Viglione, Giromini, Gustafson, & Meyer, 2014;Wood, Garb, Nezworski, Lilienfeld, & Duke, 2015), and applied them on several samples from different countries (DzamonjaIgnjatovic, Smith, Djuric Jocic, & Milanovic, 2013;Moore, Viglione, Rosenfarb, Patterson, & Mausbach, 2013;Silva & Costa, 2014). Valkonen, Lindfors, and Knekt (2012) used the Ego Impairment Index, EII, to study anxiety disorders, and found a significant, but weak association between the EII and the interview-based scale Level of Personality Organization, LPO, (Pyykkönen, 2008, apud Valkonen et al, 2012.…”
mentioning
confidence: 99%